Course management systems: Time for users to get what they need - Hannafin, Robert D.; Ioannou, Andri (My University, 2008)
Course management systems (CMSs) are software systems designed to manage course content and course activities. These tools (e.g., WebCT, Blackboard, ANGEL, Educator, FirstClass) integrate technological and pedagogical features into a web-based system that allows instructors, even those who are unfamiliar with web-based technologies, to design, deliver, and manage an online course. Common features of most CMSs include content areas, discussion boards, chat rooms, assignment drop boxes, quizzes and surveys, and white boards. CMSs support student-teacher communication and collaboration; students are able to share resources, collaborate, participate in forums, take online tests, access their grades, and upload assignments.
Keywords: Educational Technology; Learning and Instruction